How can state support the innovations to build sustainable competitive advantage of the country - Zaušková, Anna; Bobovnicky, Artur; Madleňák, Adam (Serbian Journal of Management, 2013)
As the crisis gets longer and deeper, growth disparities between some European regions are increasing, there is an even stronger need to accelerate innovation support and deepen it in the areas crucial to innovation, such as higher education, innovation-based entrepreneurship and demand-side measures. Europe needs fresh dynamism in its economy. Existing industries and the countries, too, need to develop new applications and new business models in order to grow and maintain their competitive advantage. This calls for an innovation-driven structural change, attracting top talent and reward innovative entrepreneurs, offering them much better opportunities to start and grow new businesses. Several studies were done exploring the innovations and their importance for the companies to achieve a sustainable competitive advantage. The article describes basic approaches and the model of relationship between key factors and their influence on the construct success of the company. As an outcome from this model it is clear that innovation orientation of the management and ability to launch innovations onto the market are central aspects of the success. The article deals with current status of innovations in Slovakia, identifying what are the preconditions for future development of the environment that is supporting innovations and how are they fulfilled in Slovakia.